Propranolol treatment during repetitive mild traumatic brain injuries induces transcriptomic changes in the bone marrow of mice - Smith, Jared A.; Nguyen, Tyler; Davis, Brittany C.; Lahiri, Debomoy K.; Hato, Takashi; Obukhov, Alexander G.; White, Fletcher A. (Frontiers in Neuroscience, 2023)
There are 1.5 million new mild traumatic brain injuries (mTBI) annually in the US with many of those impacted experiencing long-term consequences lasting months after the injury. Although the post injury mechanisms are not well understood, current knowledge indicates peripheral immune system activation as a causal link between mTBI and long-term side effects. Through a variety of mechanisms, peripheral innate immune cells are recruited to the CNS after TBI to repair and heal the injured tissue; however, the recruitment and activation of these cells leads to further inflammation. Emerging evidence suggests sympathetic nervous system (SNS) activity plays a substantial role in the recruitment of immune cells post injury. We sought to identify the peripheral innate immune response after repeated TBIs in addition to repurposing the nonselective beta blocker propranolol as a novel mTBI therapy to limit SNS activity and mTBI pathophysiology. Accordingly, tissue was isolated from bone marrow for RNA sequencing assays at 1-, 7-, and 28-days. Our data displays changes in RNA at various timepoints, most pronounced in the mTBI propranolol group, suggesting a single dose propranolol injection as a viable future mTBI therapy in the acute setting.